1995
DOI: 10.1038/376037a0
|View full text |Cite
|
Sign up to set email alerts
|

Identification and inhibition of the ICE/CED-3 protease necessary for mammalian apoptosis

Abstract: The protease responsible for the cleavage of poly(ADP-ribose) polymerase and necessary for apoptosis has been purified and characterized. This enzyme, named apopain, is composed of two subunits of relative molecular mass (M(r)) 17K and 12K that are derived from a common proenzyme identified as CPP32. This proenzyme is related to interleukin-1 beta-converting enzyme (ICE) and CED-3, the product of a gene required for programmed cell death in Caenorhabditis elegans. A potent peptide aldehyde inhibitor has been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

118
2,798
1
25

Year Published

1996
1996
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,756 publications
(2,942 citation statements)
references
References 44 publications
118
2,798
1
25
Order By: Relevance
“…One of the established substrates for caspase-3 protease in cells is poly(ADP-ribose) polymerase (PARP), which is cleaved from a 116 kDa intact protein into 85 and 31 kDa fragments during apoptosis. 17 The cleaved product (85 kDa) of PARP was detected in the lysate of TNF-a þ ActD-treated hepatocytes by Western blot (Figure 2d). PARP cleavage was almost completely inhibited by DEX pretreatment for 6 h, and this inhibition was gradually reversed by decreasing the time period of DEX pretreatment.…”
Section: Tnf-α+actdmentioning
confidence: 96%
“…One of the established substrates for caspase-3 protease in cells is poly(ADP-ribose) polymerase (PARP), which is cleaved from a 116 kDa intact protein into 85 and 31 kDa fragments during apoptosis. 17 The cleaved product (85 kDa) of PARP was detected in the lysate of TNF-a þ ActD-treated hepatocytes by Western blot (Figure 2d). PARP cleavage was almost completely inhibited by DEX pretreatment for 6 h, and this inhibition was gradually reversed by decreasing the time period of DEX pretreatment.…”
Section: Tnf-α+actdmentioning
confidence: 96%
“…37,38 The reactions were carried out at 37°C with 10 M Ac-DEVD-AMC (Alexis, San Diego, CA, USA). DEVDase activity was examined with a luminescence fluorometer (Cytofluor 2300; Millipore, Bedford, MA, USA).…”
Section: Fluorometric Assay Of Caspase-3 Activitymentioning
confidence: 99%
“…Cas-3 usually exists in the cytoplasm as an inactive precursor that becomes proteolytically activated in cells undergoing apoptosis (Schlegel et al, 1996;Wang et al, 1996). Cas-3 is activated by multiple cleavages of its 32 kDa precursor form to generate the 17/11 kDa or 20/11 kDa active forms (Nicholson et al, 1995;Wang et al, 1996). Other ®ndings that active cas-3 cleaves cas-3 has indicated that cas-3 can be activated through autocatalysis .…”
Section: Introductionmentioning
confidence: 99%